Attempt to correct grassland N2O fluxes biased by the DN-based opaque static chamber measurement. (1st November 2021) - Ma, Lei; Zhang, Wei; Zheng, Xunhua; Yao, Zhisheng; Zhang, Han; Wang, Rui; Zhu, Bo; Wang, Kai; Liu, Chunyan; Cao, Guangmin; Wang, Yanfen; Zhang, Yiping; et al.
Abstract: The DN method, referred to a gas chromatography (GC) method uses dinitrogen as a carrier gas, in combination with opaque static chamber, was widely used to measure grassland nitrous oxide (N2 O) fluxes. However the N2 O fluxes were positively biased by this method, as compared to the other GC methods. Currently, no study was conducted through simultaneous measurements of N2 O fluxes by DN and other GC methods to correct the biased fluxes by the DN-based opaque static chamber measurement in grasslands. For this purpose, DN and DN-CO2 methods (dinitrogen is also used as a carrier gas, and carbon dioxide as a make-up gas), both in combination with opaque static chambers, were compared through paired measurements in alpine pastures, including meadow as grazed pasture (MGP), ungrazed meadow (UGM), zokor mounds in meadow (ZMM), dung patches in meadow (DPM) and peat wetland as pasture (PWP). The DN method resulted in N2 O fluxes about 11.1, 12.1 and 7.5 times higher ( p  < 0.05) in MGP, UGM and ZMM, respectively, while there was no significant difference between the two methods in DPM or PWP. All the paired fluxes with DN-CO2 measurements >15 μg N m −2 h −1 showed positive correlations between the N2 O fluxes measured by the two methods ( p  < 0.0001), whereas the other measurements showed a negative linear correlation of flux differences between the two methods versus DN-measured fluxes ( p  < 0.0001). We further developed correction approaches for DN-measured fluxes and validated these corrections using the data from this study or those observed previously in different terrestrial ecosystems by other studies. The estimated annual N2 O emissions from grasslands in China would be reduced from 288.1 to 98.7–142.3 Gg N yr −1 (1 Gg = 10 9  g) if DN-measured fluxes were corrected using the approaches established in this study. We concluded that the DN method should be replaced by other GC methods or non-GC techniques to measure N2 O fluxes from terrestrial ecosystems. Moreover, our study provides a valid approach to correct DN-measured N2 O fluxes from global grasslands. Graphical abstract: X c denotes corrected DN-measured nitrous oxide (N2 O) flux (μg N m −2  h −1 ). DN is a widely used gas chromatograph (GC) method that analyzes N2 O with an electron capture detector (ECD), uses dinitrogen (N2 ) as the carrier gas but does not use a make-up gas while not filtering samples using, e.g., ascarite. The correction approaches are established for measurements of DN in combination with opaque static chambers. In b, DN and Non-DN are the N2 O fluxes obtained by DN and other GC-ECD methods, respectively, in different terrestrial ecosystems as non-hot cases. DNc1, DNc2 and DNc3 are the DN-measured N2 O fluxes corrected by (1) a previously developed approach for fertilized croplands, and the approaches established in this study based on (2) instantaneously fluxes and (3) annual and seasonal mean fluxes, respectively. Different capital letters above the bars indicate significant differences at p  < 0.05. Image 1 Highlights: Measurements by DN, a widely used GC method, largely bias N2 O fluxes of grasslands. DN should be replaced by non-DN techniques to measure N2 O emissions from soils. Approach for correcting bias of DN-measured N2 O fluxes is developed and validated. This approach is applicable for correction of DN measurements from grasslands.